Cost-effective technology of temporary setting trains aside from the traffic - E. A. Sotnikov; P. S. Kholodnyak (Вестник Научно-исследовательского института железнодорожного транспорта, 2019)
The article determines main factors of the need for modern conditions of temporary setting aside trains from the traffic, which require consideration of this operation not as an emergency forced measure, the need for which arises because of operational personnel errors, but as one of the elements of the transportation process technology that require it rational organization. These factors are: formation of large unloading areas in seaports taking into account recurring difficulties in its work, technical equipment failures and traffic safety violations, daily irregularity of train operation, etc. Principles of building a rational strategy for temporary setting aside trains from traffic are considered. It makes provision for: using the capabilities of the operational area infrastructure as a whole for set aside trains, impermissibility of reducing the carrying capacity of previous sections of the difficult section below its carrying capacity as a result of set aside trains, selecting stations for set aside trains based on feasibility studies.Use of a cost-effective strategy for the temporary setting trains from traffic in the event of operational difficulties will minimize the expenses of the JSC “Russian Railways” related to the need to carry out this element of the transportation process technology.